COMPREHENSIVE STUDY OF THE PLANT RAW MATERIAL PULMONARIA MOLLIS WULFEN EX HORNEM (BORAGINACEAE JUSS) (Experimental biology, 2025)
Studiеs оf mеdicinal flоra fоr thе presence of new biologically important components and identification of potentially significant plant species, occupy a special niche in the development of drugs based on plant raw materials. In official medicine, medicinal plants are increasingly used and prioritized in the treatment and prevention of many diseases [1]. Long-term studies of medicinal plants have shown that extracts from them have low toxicity and exhibit therapeutic properties, and the variety of biologically active substances provides a wide range of pharmacological actions of plant preparations. Based on literature data, Pulmonaria mollis is rich in polyphenolic compounds, glycosides (rosmarinic acid), naphthaquinones, terpenes, heterocyclic compounds – allantoin, and many of them have pronounced antioxidant, antibacterial and anti-inflammatory activity. A comprehensive study was conducted on the aboveground part of Pulmonaria mollis Wulfen ex Hornem., growing in the Alakol District of the Zhetysu Region, Republic of Kazakhstan. The content of biogenic ...
Keywords: Pulmonaria mollis; amino acid composition; macro and micronutrients; polyphenols; phytochemicals,; capillary electrophoresis; phytopreparation